Human Rights and Democracy in South Asia: Theory and Practice in Pakistan - Muhammad Abdullah; Manotar Tampubolon; Zaneera Malik (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Political instability in Pakistan has led to a weak and inconsistent protection of human rights, with human rights abuses being committed with impunity and limited accountability, ultimately hindering the development of a strong and sustainable democratic system. The paper gives an overview of the legal protections provided under the Constitution of Pakistan regarding fundamental human rights. The paper aims to provides an analysis of the application of various human rights regulations and the ground realities in the country. Using a variety of secondary data sources, including human rights reports, news articles, and legal documents, the paper explores the extent to which the government of Pakistan is fulfilling its obligations under national and international human rights regulations. This research paper examines the current situation of human rights in Pakistan, with a focus on key issues such as the rule of law, economic challenges, fight against corruption and terrorism, women and minority rights, and freedom of expression. The findings suggest that while there have been some positive developments in recent years, such as the strengthening of counter-terrorism measures and the creation of new laws to protect women's rights, significant challenges remain. These challenges include the failure to hold perpetrators of human rights abuses accountable, the use of legal regulations to suppress dissent and free speech, and the continued discrimination against religious minorities and marginalized groups.